2000
DOI: 10.1080/07060660009500477
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicité de huit mycotoxines associées à la fusariose de l'épi chez le blé

Abstract: Phytotoxicité de huit mycotoxines associées a la I fusariose de l'épi chez Ie blé 1 F. Eudes, A. Comeau, S. Rioux et J. CollinRésumé : L'étude de huit mycotoxines de Fusarium spp. a une série de concentrations allant de 0 a 4,3 mg/L pour Ie desoxynivalénol, Ie 3-acétyldésoxynivalénol, Ie nivalénol et un fikrat de culture, ou de 0 a 14,3 mg/L pour les toxines T2 et HT2, Ie diacétoxyscirpénol et la zéaralénone, révèle que les trichothécènes sont phytotoxiques. L'inhibition de l'élongation des coléoptiles est bie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 13 publications
(12 reference statements)
1
46
0
Order By: Relevance
“…Eudes et al (2000) demonstrated the phytotoxicity of the six trichothecenes DON, 3-acetyldesoxynivalenol (3-ADON), NIV, DAS, T-2 toxin and HT2 in four wheat cultivars Norseman, Katepwa, Toropi and Nyu-Bay. They found that DON and 3-ADON were more toxic than T-2 toxin, HT-2 and DAS, and that those toxins inhibited wheat coleoptile elongation at very low concentrations.…”
Section: Gross Toxic Effects Of Trichothecenes On Animalsmentioning
confidence: 99%
“…Eudes et al (2000) demonstrated the phytotoxicity of the six trichothecenes DON, 3-acetyldesoxynivalenol (3-ADON), NIV, DAS, T-2 toxin and HT2 in four wheat cultivars Norseman, Katepwa, Toropi and Nyu-Bay. They found that DON and 3-ADON were more toxic than T-2 toxin, HT-2 and DAS, and that those toxins inhibited wheat coleoptile elongation at very low concentrations.…”
Section: Gross Toxic Effects Of Trichothecenes On Animalsmentioning
confidence: 99%
“…Previous studies using a DON-deficient G. zeae mutant showed that DON was responsible for reduced virulence by G. zeae toward wheat (29,33). However, the role of NIV in the virulence of G. zeae has not been quantitatively analyzed, although NIV is known to be less phytotoxic than DON (11). Combinations of isogenic strains differing only in trichothecene production, such as 88-1 and a transgenic 88-1 Tri13 deletion strain or H-11 and a transgenic H-11 strain carrying the 88-1 Tri13 gene, would be appropriate for these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The first treatment consisted of a mixture of trichothecenes evaluated and reported in wheat coleoptiles (Eudes et al 2000…”
Section: Production Of Doubled Haploid Subpopulationsmentioning
confidence: 99%
“…(1 (McLean 1996;Wakulinski 1989;Eudes et al 2000). Synergistic effects of different trichothecenes have been reported, suggesting that mixtures of trichothecenes exert a stronger effect on the eukaryotic cells than would be expected from their additive effects (Jones et al 1995;Eudes et al 2001).…”
mentioning
confidence: 99%